2020
DOI: 10.1073/pnas.2008236117
|View full text |Cite
|
Sign up to set email alerts
|

Fc-mediated effector function contributes to the in vivo antiviral effect of an HIV neutralizing antibody

Abstract: Treatment of HIV infection with either antiretroviral (ARV) therapy or neutralizing monoclonal antibodies (NAbs) leads to a reduction in HIV plasma virus. Both ARVs and NAbs prevent new rounds of viral infection, but NAbs may have the additional capacity to accelerate the loss of virus-infected cells through Fc gamma receptor (FcγR)-mediated effector functions, which should affect the kinetics of plasma-virus decline. Here, we formally test the role of effector function in vivo by comparing the rate and timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 42 publications
1
64
0
Order By: Relevance
“…Effector immune cells, most commonly natural killer (NK) cells, bind to the antibodies via Fc receptors on their surface and then undergo degranulation releasing perforin and granzyme lysing infected cells. ADCC has been observed after infection with a number of viral pathogens ( Garcia et al, 2006 ; He et al, 2016 ; Singh et al, 2018 ), and it has been demonstrated to be an important component of protective immunity against HIV-1 ( Asokan et al, 2020 ; Haynes et al, 2012 ; Su et al, 2019 ), Influenza ( Gao et al, 2020b ; Zheng et al, 2020 ), Ebola ( Wagstaffe et al, 2019 ) and may have a role in other viral infection ( Chen, 2020 ). Since little is known about the role of ADCC in SARS-CoV-2 infections, we developed a functional SARS-CoV-2 spike (S) protein-based ADCC assay to assess the development and kinetics of antibodies after SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Effector immune cells, most commonly natural killer (NK) cells, bind to the antibodies via Fc receptors on their surface and then undergo degranulation releasing perforin and granzyme lysing infected cells. ADCC has been observed after infection with a number of viral pathogens ( Garcia et al, 2006 ; He et al, 2016 ; Singh et al, 2018 ), and it has been demonstrated to be an important component of protective immunity against HIV-1 ( Asokan et al, 2020 ; Haynes et al, 2012 ; Su et al, 2019 ), Influenza ( Gao et al, 2020b ; Zheng et al, 2020 ), Ebola ( Wagstaffe et al, 2019 ) and may have a role in other viral infection ( Chen, 2020 ). Since little is known about the role of ADCC in SARS-CoV-2 infections, we developed a functional SARS-CoV-2 spike (S) protein-based ADCC assay to assess the development and kinetics of antibodies after SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Because high levels of ADCC have been associated with slowed HIV progression, better viral control, and lower viral set points, 20,28,29,[31][32][33]44 we attempted to maximize the ADCC activity of AAV-delivered IgG by combining Fc mutations known to enhance ADCC with a1-6 fucose removal. Could the combination possibly be additive?…”
Section: Discussionmentioning
confidence: 99%
“…High levels of ADCC have been associated with slowed progression, better viral control, and lower viral set points. [28][29][30][31][32][33] Glycoengineering has also been successful at enhancing the potency of anti-HIV mAbs; when b12 was produced devoid of fucoslyation, 10-fold higher levels of viral inhibition were observed when compared to wild-type b12. 34 ADCC has also been suggested to be effective in the clearance of reactivated latent HIV-1 reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the results by Wang and colleagues reviewed above, animals treated with unmodified VRC07-523-LS had a 21% greater decline in plasma viral load than that of the Fc null group. Unexpectedly, the DEL variant induced necroptosis on FcγR bearing cells, leading to the pronounced depletion of NK cells, monocytes, and mDCs from the blood over the first day post treatment and yielding an Fc functional null phenotype with blood viremia matching that of the LALA group ( 108 ).…”
Section: Cultivating Bnab Development For Treatment and Preventionmentioning
confidence: 99%